Knowledge and perception about tuberculosis among children attending primary school in Ntcheu District, Malawi - Nyasulu P; Kambale S; Chirwa T; Umanah T; Singini I; Sikwese S; Banda HT; Banda RP; Chimbali H; Ngwira B; Munthali A (Journal of Multidisciplinary Healthcare, 2016)
Peter Nyasulu,1,3 Susan Kambale,2 Tobias Chirwa,3 Teye Umanah,3 Isaac Singini,4 Simon Sikwese,5 Hastings T Banda,6 Rhoda P Banda,7 Henry Chimbali,8 Bagrey Ngwira,9 Alister Munthali10 1Department of Public Health, School of Health Sciences, Monash University, Johannesburg, South Africa; 2World Health Organization, Country Office, Lilongwe, Malawi; 3School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa; 4Johns Hopkins Research Project, College of Medicine, University of Malawi, 5Pakachere Institute of Health and Development Communication, Blantyre, 6Research for Equity and Community Health (REACH) Trust, Lilongwe, 7National Tuberculosis Control Program, Community Health Sciences Unit, Ministry of Health, Lilongwe, 8Health Promotion Section, Ministry of Health, Lilongwe, 9Department of Community Health, College of Medicine, University of Malawi, Blantyre, 10Centre for Social Research, University of Malawi, Zomba, Malawi Background: Knowledge and perceptions about tuberculosis (TB) can influence care-seeking behavior and adherence to treatment. Previous studies in Malawi were conducted to assess knowledge and attitudes regarding TB in adults, with limited data on knowledge in children. Objectives: This study assessed knowledge and perceptions about TB in children aged 10–14 years attending primary school in Ntcheu District, Malawi. Design: A cross-sectional study was conducted in four primary schools in Ntcheu District. Data on knowledge and perception of TB were collected using a structured questionnaire. Pearson chi-square test was used to determine the association between socioeconomic factors and TB knowledge and perception. A P<0.05 was considered significant. Results: The study found that the learners had high knowledge regarding the cause, spread, and TB preventive measures. Almost 90% of learners knew that TB is caused by a germ, however, a lower proportion knew about TB symptoms ie, night sweats (49%) and enlarged cervical lymph nodes (40%). We found that 68% of learners did not know the duration of anti-TB treatment. No association was found between age, learners' grade, and knowledge (P>0.05). Conclusion: Lack of knowledge regarding TB and gaps identified, may be due to a deficiency in the content of the school curriculum or the availability of information, education, and communication materials. This is the first study to report on knowledge and perceptions of TB among primary school learners in Malawi. These results will inform the development of relevant information, education, and communication materials to enhance awareness about TB among school going children. Keywords: tuberculosis, knowledge, perceptions, health seeking, adherence, Malawi